Determining optimal needle size for decompression of tension pneumothorax in children - a CT-based study - Leonhard, Georg; Overhoff, Daniel; Wessel, Lucas; Viergutz, Tim; Rudolph, Marcus; Schöler, Michael; Haubenreisser, Holger; Terboven, Tom (Scandinavian journal of trauma, resuscitation and emergency medicine, 2019)
For neonates and children requiring decompression of tension pneumothorax, specific recommendations for the choice of needle type and size are missing. The aim of this retrospective study was to determine optimal length and diameter of needles for decompression of tension pneumothorax in paediatric patients.
Gesehen am 13.12.2019